Evaluation of tensile strength variability in fiber reinforced composite rods using statistical distributions - Hao Qin; Thierno Aliou Ka; Xiang Li; Kangxin Sun; Kaiqiang Qin; Sarkar Noor E Khuda; T. Tafsirojjaman (Frontiers in Built Environment)
Fiber Reinforced Polymer (FRP) composites are known for their exceptional resistance to harsh conditions, impressive durability, and high tensile strength, making them increasingly popular in structural applications. However, the inherent variability of composite materials poses a critical challenge, particularly in tensile strength, which directly impacts the safety and durability of structures. This study evaluated the tensile strength of 395 specimens, including 103 carbon fiber-reinforced polymer (CFRP) rods and 293 hybrid glass-carbon FRP (HFRP) rods, tested according to the GB 30022–2013 standard. To analyze the data, four statistical distributions—normal, lognormal, Weibull, and Gamma—were applied, and a goodness-of-fit test identified the Weibull distribution as the most suitable model. The study further proposed standardized tensile strength values of 2,912.40 MPa for 5 mm CFRP rods and 2,230.98 MPa, 2,385.12 MPa, and 2,517.44 MPa for 6, 7, and 8 mm HFRP rods, respectively. These findings provide valuable insights into the tensile performance of FRP rods, contributing to enhanced design and safety standards for FRP-based structural elements and offering practical references for mitigating material variability in construction applications.